Selective Electrooxidation of Glycerol Into Value-Added Chemicals: A Short Overview - Coutanceau, Christophe; Baranton, Stève; Kouamé, Roméo S. Bitty (Frontiers in Chemistry, 2019)
A comprehensive overview of the catalysts developed for the electrooxidation of glycerol with the aim of producing selectively value-added compounds is proposed in the present contribution. By presenting the main results reported in the literature on glycerol electrooxidation in acidic and alkaline media, using different kinds of catalytic materials (monometallic catalysts based on platinum group metals and non-noble metals, multimetallic alloys, or modification of surfaces by adatoms, etc.) and under different experimental conditions, some general trends concerning the effects of catalyst composition and structure, of reaction medium and of the electrode potential to enhance the activity for the glycerol oxidation reaction and of the selectivity toward a unique value-added product will be presented and discussed. The objective is to provide a guideline for the development of electrochemical systems which allow performing the electrooxidation of glycerol at the rate and selectivity as high as possible.